Building effective service linkages in primary mental health care: a narrative review part 2 - Parker Sharon; Holdsworth Louise; Perkins David; Fuller Jeffrey D; Kelly Brian; Roberts Russell; Martinez Lee; Fragar Lyn (BMC, 2011)
Abstract Background Primary care services have not generally been effective in meeting mental health care needs. There is evidence that collaboration between primary care and specialist mental health services can improve clinical and organisational outcomes. It is not clear however what factors enable or hinder effective collaboration. The objective of this study was to examine the factors that enable effective collaboration between specialist mental health services and primary mental health care. Methods A narrative and thematic review of English language papers published between 1998 and 2009. An expert reference group helped formulate strategies for policy makers. Studies of descriptive and qualitative design from Australia, New Zealand, UK, Europe, USA and Canada were included. Data were extracted on factors reported as enablers or barriers to development of service linkages. These were tabulated by theme at clinical and organisational levels and the inter-relationship between themes was explored. Results A thematic analysis of 30 papers found the most frequently cited group of factors was "partnership formation", specifically role clarity between health care workers. Other factor groups supporting clinical partnership formation were staff support, clinician attributes, clinic physical features and evaluation and feedback. At the organisational level a supportive institutional environment of leadership and change management was important. The expert reference group then proposed strategies for collaboration that would be seen as important, acceptable and feasible. Because of the variability of study types we did not exclude on quality and findings are weighted by the number of studies. Variability in local service contexts limits the generalisation of findings. Conclusion The findings provide a framework for health planners to develop effective service linkages in primary mental health care. Our expert reference group proposed five areas of strategy for policy makers that address organisational level support, joint clinical problem solving, local joint care guidelines, staff training and supervision and feedback.